2017
DOI: 10.1016/j.fct.2016.12.006
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of hazardous chemicals in edible insects and insect-based food intended for human consumption

Abstract: Due to the rapid increase in world population, the waste of food and resources, and non-sustainable food production practices, the use of alternative food sources is currently strongly promoted. In this perspective, insects may represent a valuable alternative to main animal food sources due to their nutritional value and sustainable production. However, edible insects may be perceived as an unappealing food source and are indeed rarely consumed in developed countries. The food safety of edible insects can thu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
86
4
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 185 publications
(128 citation statements)
references
References 34 publications
9
86
4
4
Order By: Relevance
“…Studies on the level of organic and metal contaminants ( e.g . polychlorinated biphenyl, DDT, dioxin compounds, heavy metals) in both whole edible insects and insect‐based food items in Belgium found that all contaminant levels were generally lower than that was found in other common animal products (Poma ). This study indicates that consuming insects presents no more of a microbial or contaminant risk than consuming other meat sources, when the same good practice standards of preparation are applied.…”
Section: Hurdles To the Use Of Insects As Food And Feedmentioning
confidence: 96%
“…Studies on the level of organic and metal contaminants ( e.g . polychlorinated biphenyl, DDT, dioxin compounds, heavy metals) in both whole edible insects and insect‐based food items in Belgium found that all contaminant levels were generally lower than that was found in other common animal products (Poma ). This study indicates that consuming insects presents no more of a microbial or contaminant risk than consuming other meat sources, when the same good practice standards of preparation are applied.…”
Section: Hurdles To the Use Of Insects As Food And Feedmentioning
confidence: 96%
“…Poma et al. () tested insects and insect‐derived products placed on the market for 12 different PCBs compounds. The concentration detected in cricket‐derived products showed that they were within the safe margins of PCBs levels according to EU legislations.…”
Section: Chemical Hazardsmentioning
confidence: 99%
“…Other studies suggest that the Orthoptera genus is less efficient in bioaccumulation of PCBs compared with Coleoptera (Blankenship et al, 2005). Poma et al (2017) tested insects and insect-derived products placed on the market for 12 different PCBs compounds. The concentration detected in cricket-derived products showed that they were within the safe margins of PCBs levels according to EU legislations.…”
Section: 3mentioning
confidence: 99%
“…Recently, chemical hazards on edible insect and their detection were shown [61]. Apart from the environmental contaminations and the possibility for several chemicals to accumulate in the farmed insect, the levels of contamination were relatively low and concentrations were similar or lower than those measured in commonly eaten animal products, such as meat, fish, and eggs.…”
Section: Potential Hazards Identificationmentioning
confidence: 92%